Emily D. West and the "Yellow Rose of Texas" myth - Tucker, Phillip Thomas, 1953- (McFarland & Company, Inc., Publishers, 2014)
"The real Yellow Rose was an ordinary but also quite remarkable free Black woman from the North, Emily D. West. This is the first full-length biography of her--which explores the evolution of one of the most popular myths in American, Texas and Western history"--